2012
DOI: 10.1128/aac.00187-12
|View full text |Cite
|
Sign up to set email alerts
|

Dual Roles of FmtA in Staphylococcus aureus Cell Wall Biosynthesis and Autolysis

Abstract: The fmtA gene is a member of the Staphylococcus aureus core cell wall stimulon. The FmtA protein interacts with ␤-lactams through formation of covalent species. Here, we show that FmtA has weak D-Ala-D-Ala-carboxypeptidase activity and is capable of covalently incorporating C14-Gly into cell walls. The fluorescence microscopy study showed that the protein is localized to the cell division septum. Furthermore, we show that wall teichoic acids interact specifically with FmtA and mediate recruitment of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(60 citation statements)
references
References 55 publications
0
60
0
Order By: Relevance
“…It was also recently observed that TarS deletion resulted in the sensitization of MRSA to β-lactam antibiotics, whereas TarM deletion did not alter the resistance phenotype (27). These authors propose that β-O-GlcNAc may act as a scaffold for recruitment of PBP2a, a protein largely responsible for MRSA, based on the recent finding that PBP2a directly binds WTA in vitro (47). As such, the preliminary result that fondaparinux shows higher affinity binding to TarM/TarS compared with its native substrate, WTA, may present an interesting avenue for drug design aimed at MRSA resensitization.…”
Section: Discussionmentioning
confidence: 99%
“…It was also recently observed that TarS deletion resulted in the sensitization of MRSA to β-lactam antibiotics, whereas TarM deletion did not alter the resistance phenotype (27). These authors propose that β-O-GlcNAc may act as a scaffold for recruitment of PBP2a, a protein largely responsible for MRSA, based on the recent finding that PBP2a directly binds WTA in vitro (47). As such, the preliminary result that fondaparinux shows higher affinity binding to TarM/TarS compared with its native substrate, WTA, may present an interesting avenue for drug design aimed at MRSA resensitization.…”
Section: Discussionmentioning
confidence: 99%
“…The WTA ␤-O-GlcNAc may serve as a scaffold for the cell wall synthesis complex or cell wall-associated proteins that directly or indirectly modulate PBP2a activity (Brown et al, 2012). Along this line there is evidence that PBP2a and PBP4 interact with WTA (Atilano et al, 2010;Qamar and Golemi-Kotra, 2012). However, it is also possible that WTA glycosylation affects the physicochemical properties of the peptidoglycan matrix by influencing the cell wall milieu (Sutcliffe, 2012).…”
Section: Functional Roles Of Wta Glycosylation In S Aureusmentioning
confidence: 93%
“…The only tolerated acceptor substrate is poly(RboP)-WTA. (37). Polyvalent scaffolding by glycopolymers (glycolipids and glycoproteins) is a known mechanism for organizing proteins in a variety of biological processes (38,39).…”
Section: Discussionmentioning
confidence: 99%